Competencies Elements for Vocational Teachers of Learners with Special Educational Needs: A Systematic Literature Review Analysis - Mohd Saad @ Zakaria, Mohd Farizan bin; Huey, Chia Jong; Suhairom, Nornazira binti; Saud, Muhammad Sukri bin; Salleh, Salmalina binti (Journal of ICSAR, 2024)
A nationally aligned education is expected to help impaired pupils attain their full potential. In recent years, there has been an increase in global awareness and recognition of vocational education and training for disabled learners. This includes regulatory changes in special needs education, creating specific curriculum curricula for fast-paced businesses, incorporating technology into lessons, constructing new vocational special needs education facilities, and reorganizing existing facilities to match current demands. These vocational education programs necessitate the creation of new vocational special needs education teaching positions. Teachers contribute to the Malaysian Education Blueprint 2012-2025 goal and vision by developing talent in special needs education. The competencies of this new educational function and other quality indicators in Malaysia have yet to be identified. This study looks at special education and vocational teacher competencies. A systematic literature evaluation revealed competencies for special education vocational teachers. Professional competency conceptions encompass technical, non-technical, personal, mental, and physical traits, motivations, and self-concept. These findings could be utilized to prepare special education vocational teachers. The findings will influence vocational special needs secondary school vocational teachers' professional growth. Identifying crucial competency features will give baseline data for enhancing our understanding of critical components for quality vocational teachers, critical to effective teaching and learning for learners with special educational needs.